Current Incidence and Contamination Sources of Ascariasis in Japan - Kagawa, Chisato; Araki, Jun; Asakura, Hiroshi; Morishima, Yasuyuki; Miguchi, Yuji; Sugiyama, Hiromu; Komatsu, Noriyuki; Kawakami, Yasushi; Iwaki, Takashi; Ikuno, Hiroshi (Food Hygiene and Safety Science (Shokuhin Eiseigaku Zasshi), 2020)
Ascaris lumbricoides or roundworm is one of the key soil-transmitted helminths affecting humans. A small number of infections continue to occur in Japan, suggesting plant foodstuff contamination as the source of infection. To understand the current status of ascariasis incidence and to identify potential sources of infection, we extensively surveyed the available literature and collected data from testing facilities that examined clinical samples or foodstuffs. We observed that from 2002 onwards, there was a decrease in the number of ascariasis cases reported in scientific journals. Data from a clinical testing facility indicated that the number of detected cases declined remarkably from 2009. Foodstuff testing facilities reported that 11 of 10,223 plant foodstuff specimens were contaminated with anisakid nematodes but not with Ascaris. Imported kimchi was suspected as the most probable source of ascarid nematode infection, as one Ascaris egg-positive sample was detected among 60 kimchi samples in a testing facility. Therefore, the sources of Ascaris infection are still not fully known and need to be clarified to establish preventive countermeasures to safeguard Ascaris infections that continue to occur in Japan.